Motion trajectory measurement of explosively-driven flyer by detonator based on multi-point velocity testing - Sun, Ya-Nan; Wu, Shen-Jiang; Ni, Yun-Kun; Wang, Ke-Xuan (Frontiers in Physics, 2025)
The motion trajectory of the flyer plays a crucial role in evaluating the shock detonation performance in detonator experiments. We used a multi-point Photon Doppler Velocimetry device to measure the flyer’s motion trajectory. When the flyer’s free surface deforms, the optical axis forms an instantaneous angle with the normal velocity at the reflected spot, causing the spot to undergo a moving displacement. The average velocity of this displacement has components both along and perpendicular to the optical axis. The velocity component perpendicular to the optical axis does not affect the beat frequency of the reflected spot along the beam path. However, the optical phase difference changes with the displacement on the surface, representing the instantaneous average velocity of the normal displacement. The tilt angle can be obtained by combining the velocity vector along the beam path with the normal velocity vector. The normal displacement and tilt angle from the detection point, along with the detection azimuth of each laser probe, are used to calculate the multi-point three-dimensional coordinates of the flyer as it changes in space over time. The coordinates affected by noise are corrected using Kalman filtering, and curved surfaces are drawn to obtain the motion trajectory as it changes with time. Based on the flyer’s deformation characteristics and the limitations of the Doppler shift, we analyze and model the signal data obtained from the detonator explosion experiment. This algorithm provides theoretical support for evaluating the shock detonation performance of different micro-charged columns by studying the explosively driven flyer.